Visual estimates of blood loss by medical laypeople: Baseline data - Prytz, Erik (Linköping University, 2020)
The data material was collected in a controlled experiment that investigated the ability of laypeople to visually assess blood loss and to examine factors that may impact accuracy and the classification of injury severity. A total of 125 laypeople watched 78 short videos each of individuals experiencing a hemorrhage. Victim gender, volume of blood lost, and camera perspective were systematically manipulated in the videos.

The data set consists of four variables: volume estimate, volume error, response time, and classification.

Each variable has a separate sheet in the excel document.

The data is from 125 individuals, each listed on a separate row with a unique ID for each individual.
Each sheet includes the participant ID (anonymous number), age in years, participant sex (0 = male, 1 = female), perspective of the video clip (0 = top view, 1 = front view), and then one column for each victim gender and loss volume combination (24 total). The column label consists of M or F for male and female victim, followed by underscore and the loss volume (e.g., M_50 for male victim with 50 ml of blood loss, or F_1100 for a female victim with 1100 ml of blood loss).

Volume estimates are the participants' estimate of blood loss in ml.
Volume error is the estimate minus the true value, in ml.
Response time is the time it took for participants to classify the bleeding as life-threatening or not, in seconds.
Classification is a value from 0 to 1 for the proportion of times the participant classified that particular gender-volume combination as depicting a life-threatening blood loss .

Detta dataset samlades in för en studie som undersökte lekmäns förmåga att göra bedömningar av storlek och allvarlighet av blodförlust. Data samlades in från 125 personer som bedömde blodförlusten på patienter i 78 filmer. Patientens kön, blodförlustvolymen, och kameraperspektivet manipulerade systematiskt.

Detta dataset har fyra variabler: volume estimate, volume error, response time, och classification. Varje variabel återfinns på varsin flik i excel-arket.

Det är 125 individer listade, en för varje rad och med ett unikt, anonymt ID. Tre individer saknar data för de variabler som ingår i detta dataset. Varje flik har också en kolumn för deltagarens kön (0 = man, 1 = kvinna), ålder i år, och perspektivet på de videofilmer deltagaren såg på (0 = vy uppifrån, 1 = vy framifrån).

För varje variabel finns därefter 24 kolumner med data för alla kombinationer av den skadade patientens kön (man eller kvinna) och de 12 blodförlustvolymer som användes (från 0 till 1900 ml). Varje kolumn har ett namn som beskriver kombinationen enligt följande struktur: M eller F för patientens kön (male och female, respektive), understreck, därefter en siffra som visar blodförlust i ml. T.ex. är M_50 en manlig patient med 50 ml blodförlust och F_1100 en kvinnlig patient med 1100 ml blodförlust.

Variabeln volume estimate är deltagarens uppskattning av blodförlust i ml.
Variabeln volume error är uppskattningen minus den sanna volymen, i ml.
Variablen response time är tiden det tog för deltagaren att klassa blödningen som antingen livshotande eller icke-livshotande, i sekunder.
Variabeln classification är ett värde från 0 till 1 som visar hur frekvent deltagaren klassade just den kön-volym kombinationen som en livshotande blödning (av tre gånger).
Visual estimates of blood loss by medical laypeople: Baseline data
Keywords: applied psychology; tillämpad psykologi; perception; varseblivning; first aid; första hjälpen; Other Clinical Medicine; Annan klinisk medicin; Applied Psychology; Tillämpad psykologi